2008
DOI: 10.1128/iai.00109-08
|View full text |Cite
|
Sign up to set email alerts
|

CD46 Contributes to the Severity of Group A Streptococcal Infection

Abstract: Streptococcus pyogenes (group A Streptococcus) is a human pathogen that causes a wide variety of diseases ranging from uncomplicated superficial infections to severe infections such as streptococcal toxic shock syndrome and necrotizing fasciitis. These bacteria interact with several host cell receptors, one of which is the cell surface complement regulator CD46. In this study, we demonstrate that infection of epithelial cells with S. pyogenes leads to the shedding of CD46 at the same time as the bacteria induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 55 publications
(59 reference statements)
3
35
0
Order By: Relevance
“…Compared to such models, the s.c. inoculation into both hind footpads in the present study was a simple procedure, and the obtained data showed a narrow dispersion of reproducibility. A recent study demonstrated that infection in epithelial cells with GAS led to the shedding of human CD46 at the same time as bacterium-induced apoptosis and cell death occurred (30). In the present study, the amount of bacterial load in the PLN of CD46 Tg mice was the same as that of non-Tg mice 48 h after s.c. infection (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Compared to such models, the s.c. inoculation into both hind footpads in the present study was a simple procedure, and the obtained data showed a narrow dispersion of reproducibility. A recent study demonstrated that infection in epithelial cells with GAS led to the shedding of human CD46 at the same time as bacterium-induced apoptosis and cell death occurred (30). In the present study, the amount of bacterial load in the PLN of CD46 Tg mice was the same as that of non-Tg mice 48 h after s.c. infection (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…It was demonstrated that during 6 h of incubation, the growth of GAS was enhanced in the cell culture medium mixed with an equal volume of mouse whole blood containing soluble human CD46 (30). Then, we examined the changes in expression of sagA (streptolysin S; SLS) of GAS472 during 6 h of incubation under the above experimental conditions.…”
Section: Matsui Et Al Infect Immunmentioning
confidence: 99%
See 2 more Smart Citations
“…CD46 interacts with adenovirus 18 , human herpes virus 6 19 , pathogenic Neisseria [20][21][22] , measles virus 23 and Streptococcus pyogenes. 24 Infection of epithelial cells by N. gonorrhoeae and S. pyogenes triggers shedding of CD46 25,26 . Although CD46 is expressed in human gastric epithelium 27 , the role of CD46 in H. pylori infection has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%